Optimality condition and duality in multi objective programming with generalized (φ,ρ)-univexity - Ojha, Deo Brat (Kathmandu University Journal of Science Engineering and Technology, 2011)
In this paper, we extend the classes of generalized type I vector valued functions introduced by Aghezzaf and Hachimi[1] to generalized univex type I vector-valued functions and consider a multiobjective optimization problem involving generalized type I function with (φ,r ) -univexity. A number of Kuhn-Tucker type sufficient optimality conditions are obtained for a feasible solution to be an efficient solution. The Mond-Weir and general Mond-Weir type duality results are also presented.